Ab initio calculations of doped TiO2 anatase (101) nanotubes for photocatalytical water splitting applications. (February 2016) - Lisovski, Oleg; Chesnokov, Andrei; Piskunov, Sergei; Bocharov, Dmitry; Zhukovskii, Yuri F.; Wessel, Michael; Spohr, Eckhard
Abstract: TiO2 (titania) is one of the promising materials for photocatalytic applications. In this paper we report on recently obtained theoretical results for N and S doped, as well as N+S co-doped 6-layer (101) anatase nanotube (NT). First principles calculations in our study have been performed using a modified B3LYP hybrid exchange-correlation functional within density functional theory (DFT). Here we discuss the energy of defect formation mechanism and electronic band structure for nanotubes under study. We also report on influence of dopant concentration on the NT's band structure and discuss the defect–defect interactions.